(untitled) (Research, Society and Development, 2020)
The environmental sustainability of the Uriboquinha stream small watershed, with the presence of a sanitary landfill in its domains, involves hydrological quantification and several environmental controls. The goal of the present research was hydrological data generate with a new approach to the climatological water balance by adapting the methodology of Thornthwaite and Mather. The methodology originally developed the indirect water balance, starting only from precipitation and evapotranspiration as hydrological variables. However, because of flow is a fundamental hydrological variable, it was introduced as one of the water components involved in the balance. Therefore, the flow, by saline tracer methodology, was monitored for a period of one year (May/18 to Apr/19). With the water balance built, it was found that there was a long length of time with water exceedance (May/18, Aug/18, Sep/18 and Dec/18 to Apr/19) and a short length of time with water deficiency (Jun/18, Jul/18 and Oct/18). The proposed method showed the contribution of each variable in the water balance, where the increase in flow directly represents the outflow of water in the basin through the base runoff and direct runoff. The resulting water balance indicated local conditions consistent with reality, with predominance of high rainfall, showing itself as a methodology that can be used for studies involving polluting activities and their respective environmental monitoring.